2020
DOI: 10.31083/j.rcm.2020.03.135
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular effects of waterpipe smoking: a systematic review and meta-analysis

Abstract: Waterpipe smoking has developed into a major and rapidly growing global tobacco epidemic affecting more than 100 million people worldwide. This study identifies and analyzes comprehensively all available data on the cardiovascular effects of waterpipe smoking. Databases PubMed, EMBASE, Web of Science, and the Cochrane Library were searched for studies published until December 2019 assessing cardiovascular effects of waterpipe smoking. We included experimental, cohort, cross-sectional and case-control studies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Waterpipe users often perceive that this form of tobacco inhalation is less injurious to health compared with conventional cigarette-smoking [ 28 ]. Nevertheless, scientific evidence has also shown that the health-hazards of waterpipe-use are similar to those of cigarette-smoking [ 29 ]; and waterpipe-usage is “a global public health problem” [ 25 ]. Mokeem et al [ 30 ] reported that clinical and radiographic parameters of periodontal inflammation are poorer in cigarette-smokers and waterpipe-users than never-smokers with no statistically significant difference between the former groups (cigarette-smokers and waterpipe-users).…”
Section: Introductionmentioning
confidence: 99%
“…Waterpipe users often perceive that this form of tobacco inhalation is less injurious to health compared with conventional cigarette-smoking [ 28 ]. Nevertheless, scientific evidence has also shown that the health-hazards of waterpipe-use are similar to those of cigarette-smoking [ 29 ]; and waterpipe-usage is “a global public health problem” [ 25 ]. Mokeem et al [ 30 ] reported that clinical and radiographic parameters of periodontal inflammation are poorer in cigarette-smokers and waterpipe-users than never-smokers with no statistically significant difference between the former groups (cigarette-smokers and waterpipe-users).…”
Section: Introductionmentioning
confidence: 99%
“…The risks of hookah smoking are often undermined due to various misconceptions, such as the use of flavouring agents in tobacco products and the false public opinion that hookah is healthy because the hazardous agents in the tobacco are filtered through the water inside the tank 3 . Nonetheless, hookah is similar to cigarettes in terms of causing diseases such as cancer, respiratory and gastrointestinal disorders, chronic pulmonary diseases and cardiovascular diseases 4,5 . Furthermore, the persistent use of hookah could lead to nicotine dependency 6,7 …”
Section: Introductionmentioning
confidence: 99%
“… 3 Nonetheless, hookah is similar to cigarettes in terms of causing diseases such as cancer, respiratory and gastrointestinal disorders, chronic pulmonary diseases and cardiovascular diseases. 4 , 5 Furthermore, the persistent use of hookah could lead to nicotine dependency. 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
“…Besides traditional risk factors, tobacco smoking has been considered a significant cause of CVD [ 1 , 3 , 4 , 5 ]. Whether it is passive or active smoking, cigarettes, or other nicotine-delivery systems like waterpipes or non-smoke tobacco, they all share most of the harmful effects on the heart and blood vessels [ 3 , 4 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides traditional risk factors, tobacco smoking has been considered a significant cause of CVD [ 1 , 3 , 4 , 5 ]. Whether it is passive or active smoking, cigarettes, or other nicotine-delivery systems like waterpipes or non-smoke tobacco, they all share most of the harmful effects on the heart and blood vessels [ 3 , 4 , 6 ]. The mechanism by which tobacco consumption causes this massive damage is multifactorial, ranging from containing many chemicals that disrupt cellular function to the oxidative stress and inflammation of approximately every tissue type in the human body [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%